(untitled) (Circe de clásicos y modernos, 2020)
This paper deals with Menippus or Necromancy of Lucian of Samosata, a satiric dialogue on Menippus’ katabasis (descending to the underworld) to discover the best form of the human life. The issue articulates two generic traditions taking into account, on the one hand, the katabasis has taken shape in different mythological stories, and on the other hand, the quest for the best kind of the human life is a philosophic topic par excellence. Since both traditions were historically understood in tension: the myth on the side of pleasant writing; and the philosophy of writing aimed at utility, in Necromancy two paths are presented to solve such aporia. The problem arises from disavowal that the myth has obtained to deal with problems attributed philosophy as the existential question. To tackle this paradox the references and treatment given to the two traditions are analysed. Its purpose is to revise the tension based on the recognition in lucianic writing of a resignification of the myth by its conceptual skill in the formation of satire. The study delves into the impossibility of a monological vision because the aporia needs of both traditions. In this way, Lucian erases the limits of generic traditions and produces an answer to the serious intellectual problem with a mythical formulation that inscribes it in a system of creative writing.